Gender difference in motives of knowledge searching: Measurement invariance and factor mean comparison of the interest/deprivation epistemic curiosity - Duan Huang; Mingjie Zhou; Li Wang; Jianxin Zhang (2010 IEEE 2nd Symposium on Web Society, 2010)
Epistemic Curiosity, the urge for new information, is an emerging construct that can be applied in IT field. The purpose of the present study was to examine the factor structure and factorial invariance of the revised interest/deprivation epistemic curiosity model (I/D EC model) in Chinese cohorts of male and female students. The Chinese version of the revised I/D EC Scale was administered to 2,653 students from 7 junior high schools. Confirmatory factor analysis and multiple-groups confirmatory factor analysis were conducted to assess the structure and the measurement invariance of the scale. The results showed that a 2-factor model best characterizes the structure of the scale, and a strict invariance appeared to exist across genders. No practically significant gender differences were found in both I-type EC and D-type EC.